Srpski - Ćurčić, Milica; Dinić, Jelena (The Policy of National Security, 2024)
Military neutrality and cooperation are essential in realizing Serbia's national interests, manifested in preserving sovereignty, independence, and territorial integrity. The creators of strategic documents in the area of national security have placed the unlawfully declared independence of Kosovo and Metohija and the activities of extremist groups in that territory within the cluster of the most significant security threats endangering Serbia. By identifying basic concepts from existing national security strategies as overarching documents for analyzing the Republic of Serbia's perspective and determining how these concepts are conceptualized, insights are generated regarding the national stance towards Kosovo and Metohija. A comparative analysis of segments of existing strategies based on established categories and within the segments directly or indirectly related to Kosovo and Metohija makes it possible to ascertain the success of applying defined instruments. Cooperation with other states through European integration and bilateral cooperation with states of the Western Balkans, the USA, India, Russia, and China has been elevated to the level of national interest in strategic documents. Military neutrality as part of national security policy is implicitly mentioned in strategic documents, opening a corridor for various interpretations. Formulating responsible national security policy as the ultimate goal implies a coherent approach in analyzing the complex network of relationships among actors on the international political stage and a profound understanding of the implications of these processes on realizing the national interests of Serbia.
Keywords: military neutrality; national security strategy; national interest; cooperation; European integration; security threats; Kosovo and Metohija